Investigation of endocrine and immunological response in fat tissue to hyperbaric oxygen administration in rats - Åžen, H; Erbağ, G; Ovali, M A; í–ztopuz, R í–; Uzun, M (Cellular and Molecular Biology, 2016)
Though HBO treatment is becoming more common, the mechanism of action is not fully known. The positive effects of HBO administration on the inflammatory response is thought to be a possible basic mechanism. As a result, we aimed to research whether endocrine and immunological response of fat tissue changes in rats given HBO treatment model. This research was carried out on Wistar albino rats, they were treated with hyperbaric oxygen therapy. Their fatty tissue were taken from the abdomen, gene expression of the cytokines and adipokines were analyzed with Real time PCR method. When the gene expression of hormones and cytokines by fat tissue was examined, the leptin, visfatin, TNF-Î±, IL-1Î² and IL-10 levels in the HBO treatment group were statistically significantly increased compared to the control group (p=0.0313, p=0.0156, p=0.0156, p=0.0156, p=0.0313). In conclusion, in our study we identified that HBO administration affected the endochrinological functions of fat tissue.